An Approximate Solution for the Non-Linear Fractional Schr"odinger Equation with Harmonic Oscillator - Akour, Abdulrahman N.; Jaradat, Emad K.; Al-Faqih, Ala'a M. (Discontinuity, Nonlinearity, and Complexity, 2026)
In this work, we propose an approximate solution for the nonlinear Schrödinger with harmonic oscillator by fractional calculus with Caputo definition. It is observed that the nonlinear Schrödinger equation in one and two dimensions effect on the behavior of the wave function, the result shows the technique is highly encouraging and efficient.